Principles Of Flotation, VII-Mercaptobenzthiazole As A Flotation Agent (8e157720-7109-44d2-803d-0cf477b58391) - Ian William Wark; Keith Leonard Sutherland (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1939)
MERCAPTOBENZTHIAZOLE and its sodium salt are marketed under the trade names Flotagen and Flotagen S respectively, for use as collectors for cerussite and other minerals. The structural formulas for sodium mercaptobenzthiazole and for sodium ethyl xanthate are: [ ] Chemically there is a resemblance between the two compounds, though the free acid (mercaptobenzthiazole itself) is much more stable than xanthic acid. Both are readily oxidized, e.g., by iodine to disulphides, and can be estimated by iodometric titration. Qualitatively they are similar as collectors in flotation, although there are quantitative differences between them that may be important in practice. It is deduced that the influence of the nitrogen atom is subordinated to that of the sulphur atoms, and that the dominant group of these compounds is the mercapto group -SH or -SNa. The general method of investigation has been based on contact tests. Two temperatures, 10º and 35º C., have been chosen, and with a standard concentration of 20 mg. per liter of mercaptobenzthiazole (i.e., of the free acid) the influence of alkali, cyanide and copper sulphate on contact at sulphide mineral surfaces has been studied. This standard concentration corresponds to about 19 mg. per liter potassium ethyl xanthate; it brings out the differences between the minerals better than a higher concentra-